Nemo Tenetur ilkesi ışığında ceza muhakemesi hukukunda beden muayenesi - Kılıç, Ümmügülsüm (My University, 2010)
Ceza muhakemesinde temel amaç, maddi gerçeğin hiçbir şüpheye yer vermeyecek şekilde ortaya çıkarılmasıdır. Bununla birlikte, maddi gerçeğin araştırılması, ceza muhakemesine hakim olan tek ilke olmadığı gibi, ne pahasına olursa olsun maddi gerçeğin araştırılması anlayışı da çağdaş ceza muhakemesi ilkesine aykırı düşer. Ceza muhakemesinde maddi gerçek ortaya çıkarılırken hukuka uygun delil elde etmek en önemli hususlardan biridir. Bu sebeple, çağdaş muhakeme hukuku bir yandan etkin kovuşturma yöntemleri ile maddi gerçeğe ulaşmayı hedeflerken, diğer yandan insan hakları ihlallerine yol açmamalıdır. Beden muayenesi ve vücuttan örnek alma bir yanda kişinin vücut bütünlüğüne müdahale ederken bir yandan da masumluk karinesini ve özel hayata saygı hakkını ihlal edebilecek bir tedbirdir. Anayasa’daki “kimsenin kendisini ve yakınları aleyhine delil vermeme” ilkesine aykırılık teşkil etmeden vücut muayenesi yapılması en önemli hedeflerden biridir. Aynı şekilde Ceza Muhakemesi Kanunu’nun benimsediği en temel ilkelerden olan “delilden sanığa ulaşma sistemi” gerçekleştirildiğinde, maddi gerçeğe ulaşma yolunda insan hakları ihlalleri de önemli ölçüde azaltılmış olacaktır. Nemo Tenetur 2) Muayene 3) Ceza Muhakemesi 4) Katlanma Yükümlülüğü 5) Delil

The fundamental purpose of criminal procedure is to reveal material fact without any suspicion. Yet, searching the material fact is not the only dominant principal in the criminal judgment. More importantly, the understanding of examining the material fact at any expense is at odds with the modern criminal judgment. Revealing the material fact and providing justice at the same time are very difficult process. Gathering evidence according to the rule of law is one of the most crucial factors in the criminal procedure. That is why, while modern criminal judgment aims at reaching the material fact by efficient prosecution methods, it should not lead to the human rights violations. In this respect, lawful evidence occupies the central essential position in front of the criminal procedure. Body inspection and drawing a sample from body not only intervene with body integration of person but also violate his/ her both presumption of innocence and the right to respect privacy. Inspecting body as complying with the principle of Constitution, which points out that no body should be forced to submit evidence for himself/ herself or for relatives, is one of the most crucial objectives. In a similar vein, if the system ‘from evidence to defendant’ is actualized as the basic pillar of the code or law criminal procedure , human right violations in revealing the material fact would be diminished mostly. Key Words: 1) Nemo Tenetur 2) Inspection 3) Criminal Judgment 4) Burden of endurance 5) Evidence
Keywords: Hukuk_Kamu Hukuku; Kamu Hukuku